Antiviral effect of polyphenol rich plant extracts on herpes simplex virus type 1 - Sayed A. El-Toumy; Josline Y. Salib; Walaa A. El-Kashak; Christel Marty; Gilles Bedoux; Nathalie Bourgougnon (Food Science and Human Wellness)
Evaluation of the anti-herpetic activity of 25 Egyptian plants extracts was investigated in vitro in this study. The antiviral activity against Herpes Simplex Virus type 1 (HSV-1) was done on Vero cell lines by cell viability. Only two plants extracts; namely Euphorbia coopire (Euphorbiaceae) and Morus alba (Moraceae) showed potent anti-herpetic activity and six other extracts showed moderate inhibition. In contrast, a bioassay monitored phytochemical exploration of these two plants led to the isolation of pure flavonoid compounds. The antiviral activity of the isolated compounds was also examined, among which seven pure compounds namely; 7-galloyl catechin, gallic acid, kaempferol 3-O-β-(6″-O-galloyl)-glucopyranoside, quercetin 3-O-β-(6″-O-galloyl)-glucopyranoside, curcumin, quercetin and kaempferol exhibited significant inhibition. Keywords: Egyptian plants, Anti-HSV-1, Polyphenols, Vero cell